Tensile and Impact Properties of Microcrystalline Cellulose Nanoclay Polypropylene Composites - Yousef Ahmad Mubarak (International Journal of Polymer Science)
The aim of the present work is to investigate the effects of nanoclay (NC) on the mechanical properties of polypropylene (PP)/microcrystalline cellulose (MCC) composites modified by maleic anhydride grafted PP (PP-g-MA). Polypropylene/microcrystalline cellulose nanocomposites were prepared using a twin screw Brabender Plasticorder, the weight percent of the MCC was varied at 0, 0.5, 1, 2, 5, 10, 20, and 40 wt%, and the NC content was varied at 0, 0.05, 0.1, 0.5, 1.0, and 2.0 wt%. The results showed that consistent and uniform PP/MCC nanoclay composite can be produced easily with the presence of PP-g-MA. Compression molding technique was used to produce tensile and impact testing samples; all samples were characterized by tensile and impact tests. It is observed that increasing the amount of either the MCC or the NC will decrease the tensile strength, elongation at break, and impact strength; much more reduction in the same properties was obtained in case both MCC and NC exist within PP composites. Compared with neat PP, a loss of over 75% in both elongation and impact strength was obtained for nanoclay composites which contain 60 wt% PP/40 wt% MCC. The most significant enhancement in the mechanical properties of polypropylene/microcrystalline cellulose nanocomposites is in Young’s modulus where an increment of more than twofold can be achieved for 60 wt% PP/40 wt% MCC nanocomposite. Polarized light photomicrographs showed that MCC particles play a nucleating agent rule in terms of intensity of nucleation and crystal growth acceleration.